Huge vegetation and pannus formation in haemoculture negative prosthetic mitral valve endocarditis - Ömeroğlu, Suat Nail; Göksedef, Deniz; Balkanay, Ozan Onur; Kanbur, Elmas; Yüceyar, Lale; İpek, Gökhan (Cerrahpaşa Medical Journal, 2019)
Obstruction of mechanical valve prosthesis is a rarely seen but serious complication. Prosthetic valve thrombosis, pannus formation and vegetation are leading causes of an obstructed mechanical valve prosthesis. We report a surgically treated case of haemoculture negative valve endocarditis with an obstructed mitral valve prosthesis by a huge vegetation and pannus formation. A 36-year-old male patient, who underwent an aortic and mitral valve replacement operation two years ago, was admitted to our institution with dyspnea, orthopnea, tachypnea, tachycardia and fever. Physical examination revealed pretibial edema, hepatomegaly and bilateral pulmonary crepitations. 3/6 systolic murmur was present on mitral valve area. Transthoracic and transesophageal echocardiography revealed a vegetation like mobile mass with 3,1x0,7cm in dimensions that subtotally obstructed mechanical mitral valve. Haemoculture negative prosthetic valve endocarditis was diagnosed. Antibiotherapy, that was started preoperatively, was continued 4 weeks after the operation. During the operation it was found that mechanical mitral valve prosthesis was almost totally obstructed by huge vegetation and pannus formation. Mitral valve was removed and replaced with a bileaflet mechanical valve. Inotropic support was used during the intensive care unit period. Late postoperative period was uneventful. Vegetation and pannus formations in mechanical valve prosthesis can cause severe complications. Surgical treatment combined with antibiotherapy can be used with auspicious results.